Estimating population level 24-h sodium excretion using spot urine samples in older adults in rural South Africa. Issue 2 (18th February 2023) - Du Toit, Jacques D.; Kapaon, David; Crowther, Nigel J.; Abrahams-Gessel, Shafika; Fabian, June; Kabudula, Chodziwadziwa W.; Wade, Alisha N.; Tollman, Stephen; Gaziano, Thomas A.
Abstract : Background: South Africa has introduced regulations to reduce sodium in processed foods. Assessing salt consumption with 24-h urine collection is logistically challenging and expensive. We assess the accuracy of using spot urine samples to estimate 24-h urine sodium (24hrUNa) excretion at the population level in a cohort of older adults in rural South Africa. Methods: 24hrUNa excretion was measured and compared to that estimated from matched spot urine samples in 399 individuals, aged 40–75 years, from rural Mpumalanga, South Africa. We used the Tanaka, Kawasaki, International Study of Sodium, Potassium, and Blood Pressure (INTERSALT), and Population Mean Volume (PMV) method to predict 24hrUNa at the individual and population level. Results: The population median 24hrUNa excretion from our samples collected in 2017 was 2.6 g (interquartile range: 1.53–4.21) equal to an average daily salt intake of 6.6 g, whereas 65.4% of participants had a salt excretion above the WHO recommended 5 g/day. Estimated population median 24hrUNa derived from the INTERSALT, both with and without potassium, showed a nonsignificant difference of 0.25 g ( P  = 0.59) and 0.21 g ( P  = 0.67), respectively. In contrast, the Tanaka, Kawasaki, and PMV formulas were markedly higher than the measured 24hrUNa, with a median difference of 0.51 g ( P  = 0.004), 0.99 g ( P  = 0.00), and 1.05 g ( P  = 0.00) respectively. All formulas however performed poorly when predicting an individual's 24hrUNa, Conclusion: In this population, the INTERSALT formulas are a well suited and cost-effective alternative to 24-h urine collection for the evaluation of population median 24hrUNa excretion. This could play an important role for governments and public health agencies in evaluating local salt regulations and identifying at-risk populations.